Application of Plant Anatomy Media to Improve Learning Outcomes in Science for Grade IV at SDN 065/VI Karang Berahi - Willya Syafitri; Tabroni Tabroni; Fia Alifah Putri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research aims to prove that simple tools easily found in the surroundings can help students better understand plant materials and their uses, thereby improving the learning outcomes of fourth-grade students at SDN No.065/VI Karang Berahi in the IPAS subject. This research uses the Classroom Action Research (CAR) method with the Kemmis and McTaggart model, which includes the stages of planning, action implementation, observation, and reflection. The research was conducted in two cycles. The results of the study showed an improvement in student learning outcomes in each cycle. In the pre-cycle stage, student mastery only reached 21.05%, then increased to 63.16% in cycle I, and further increased to 84.21% in cycle II. The improvement indicates that the use of simple learning media is capable of enhancing students' learning outcomes, both in the cognitive, affective, and psychomotor domains. Thus, it can be concluded that simple learning media are effective in improving the learning outcomes of fourth-grade students in the IPAS subject on plant material at SDN No.065/VI Karang Berahi.